The German labor market after the long boom: What's next? - Werner Eichhorst; Paul Marx (Institute of Labor Economics (IZA), 2025)
Germany has long been portrayed as the best real-world example of an export-oriented economic model associated with a dualized labor market and welfare state. The success of this export-centered model over the last decades has typically been ascribed to competitiveness due to wage restraint and widening wage dispersion in line with declining collective bargaining coverage. This paper starts from this widely shared perception, but sheds a new light on the dynamics and structures of employment in Germany after a long boom period for the late 2000s to the most recent period. The paper argues that much of this change is rather market driven than to be explained by institutional reforms. Employment growth was driven by service sector expansion while wage dispersion and non-standard work stagnated and declined somewhat, reducing the extent of these forms of dualisms in the labor market. Following a cyclical argument about political decision-making, we only saw limited re-regulatory activity. However, the favourable economic climate has changed more recently.
Keywords: J21; J24; J31; J38; 330; Germany; non-standard employment; dual labor markets; labor market reforms; political economy